All-in-One Molecular Aggregation-Induced Emission Theranostics: Fluorescence Image Guided and Mitochondria Targeted Chemo-and Photodynamic Cancer Cell Ablation - Guo, Bing (AMER CHEMICAL SOC, 2021)
10.1021/acs.chemmater.0c01187